Liberty as non-domination: a critical discussion - Sevinç, Tuğba. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
This thesis aims at analyzing Philip Pettit’s notion of domination with a view to examining the republican conception of political liberty as non-domination. To do so, the definition and the harms of domination are examined to comprehend political liberty as non-domination and the ways of establishing it. Pettit’s account of political liberty is criticized for being insufficient for two different reasons. First, Pettit’s notion of domination is too narrow to give a comprehensive account of political liberty as non-domination. In order to illustrate a more satisfactory account of domination; Young’s conception of domination and the relation between domination and oppression, Bartky’s view of psychological oppression, and Sen’s theory of “adaptive preference formation” are introduced. Second, Pettit’s notion of equality is criticized for being insufficient. Regarding Pettit’s claim that liberty is a matter of status equality, three forms of status equality are introduced; structural equality, material equality and cultural status equality. Since Pettit argues only for equality before the law, he is criticized for undervaluing the importance of material equality and ignoring the matters regarding cultural status equality. In order to illustrate a more satisfactory account of equality, the dialectic between three forms of equality and their relation to liberty are examined. Considering the critiques about the insufficiency of Pettit’s account of liberty, the scope of state activity is examined with the help of real world examples. When the notions of domination and equality are considered extensively, the scope of state activity must be wider than it is in Pettit’s account of liberty.
Keywords: Liberty.; Political science -- Philosophy.